Effect of pruning on the growth and development of Protea 'Pink Ice' (P. compacta R. Br. x P. susannae Phill.) - Nieuwoudt, Gerrit (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: The main purpose of producing cut flowers is to earn a satisfactory income with the first endeavour normally to increase the total number of flowers produced. This has limits due to the number of flowers that can be produced per plant or per area planted. Another method is to get the bulk of the crop in the longest possible stem length category to earn better prices. A third option is to target the seasons or times of the year when prices are naturally higher due to a positive ratio between demands and supply. Most of the protea cultivars grown commercially in South Africa flower outside the period September to January when prices and demand for proteas on the European markets are high. Previous work established that the flowering period of some protea cultivars could be modified to more favourable marketing periods through the timing of the pruning operation. Plants of Protea ‘Pink Ice’ were pruned at monthly intervals from January to December 1999. For the first crop after pruning the highest yield was achieved for plants pruned in June. Flowers borne on an autumn flush needed 4 to 6 weeks longer to complete their development than for spring flush borne flowers. However, since flower initiation in autumn occurred earlier by more than 3 months than on the spring flush, this difference in time accounted for the earlier flowering of the former in spite of a longer period to complete the flower developmental process. The effect of cropping this cultivar in a biennial system was tested against actual prices to test the validity of the finding that the June treatment resulted in the highest number of harvestable stems. It was found that the June treatment also gave the best income and the phasing of production resulting from a June pruning in a biennial cropping system fitted this cultivar the best. Orchards should be divided in two blocks with one in the ‘on year’ and one in the ‘off year’. The length of the shoot stub left after a shoot has been pruned determines the nature of the regrowth. Four-year-old plants of Protea ‘Pink Ice’ were pruned to four different bearer lengths in November 1999 or February 2000. Plants were pruned that either a half, one, two or three flush length bearers were left on the plants. Plants with the two longer categories of bearers took the shortest time to sprout buds from axillary positions on the bearers and also had the most buds developing into shoots. The longer bearers produced more flowers per plant but the average length of the flowers was shorter than the plants with shorter bearers. The average total income was more in the instance of the longer bearers due to more flowers and the earlier harvest resulting from buds sprouting earlier.